Preparation of ovarian fluid (caviar sol) of sturgeons for the use as physiological and functional ingredients in new generation food products - I. M. Chebanov; V. E. Tarasov; I. A. Dubrovskaya; S. A. Kalmanovich (Новые технологии)
The development of the modern market for food functional ingredients involves the search for new raw materials, increasing efficiency and developing innovative technological processes for their production and introduction into fortified products, and the development of marketing promotion strategies. Considering this, we have conducted the research to assess physical, chemical and technological properties of secondary resources for the production of black caviar of sturgeon fish grown in the conditions of sturgeon farms in the Krasnodar Territory. It has been shown that ovarian fluid (caviar sol) has a high biological value, which is confirmed by the presence of all essential amino acids in caviar proteins. Caviar sol also contains a complex of basic macro- and micronutrients. The results obtained confirm that this product is a physiologically functional ingredient for the production of new generation food products. A technology has been developed for disinfecting caviar sol to increase its shelf life and of the products obtained from it. The processing of ovarian fluid (caviar sol) in the anode zone during electrolysis of an aqueous solution of table salt was carried out followed by its placement in the structure of a multiple emulsion sauce. Analysis of microbiological indicators has indicated that the processing of caviar sol and the production of sauce in the form of a multiple emulsion makes it possible to ensure microbiological indicators of the finished product that meet the requirements of TR CU 021/2011.